Temporality and Confessions in Caracol y otros cuentos (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Postmodern discourse is central to Panamanian writer Enrique JaramilloLevis´ work. Its usage illustrates the need to regard conscience as the receptive  agent of a plural experience of temporality such as that of a deep psychological scope, or one which is purely perceptive, another one rooted in the imaginative process, one other spiritual, as well as a confessional dimension of time guided by the unpredictability of memory in search of universal meaning and the introspective power of art. On the other hand, Jaramillo Levis´ original approach to time is inseparable from the metaphysical questions underlying the intersection of writing and writer emerging from the act of creation. In this essay, I study both dimensions in his work Caracol y otros cuentos.
Keywords: Enrique Jaramillo Levi; Panamanian Short Story; Postmodernity; Time; Memory; Confessions